Ice Block Production Manufacturing Information System, Perum Perikanan Indonesia, Banda Aceh - Herman; Mukhtar; Ihsanuddin (Journal Dekstop Application (JDA), 2022)
Manufacturing information systems are fundamentally integrated with computer technology, where computers play dual roles in physical process control and informational data management. This research focuses on developing an ice block production management system for the State-Owned Fisheries Enterprise (PERUM Perikanan Indonesia) in Banda Aceh using Visual Basic, aiming to replace manual record-keeping with an automated solution. Through field observations of production workflows and structured interviews with operators and managers, alongside a literature review of 15 academic references, the study designed a system capable of real-time data operations (addition, modification, retrieval) and automated reporting for sales value and cost analysis. Comparative testing demonstrated a 65% reduction in data processing time (from 15 to 3 minutes per transaction) and a 92% reporting accuracy rate, surpassing the 78% accuracy of manual methods. The system reduces monthly operational costs by 52.2% (from IDR 2.3 million to IDR 1.1 million), providing a scalable digital tool to enhance transparency and decision-making in ice block manufacturing. Future enhancements could integrate machine learning for demand forecasting and mobile interfaces for real-time monitoring.